Assessment of Hyperbilirubinemia in Acute Appendicitis - Sahi, Sanjiv Kumar; Rai, Binod Kumar; Singh, Ajit; Singh, Sujit (Med Phoenix, 2023)
Introduction: Acute appendicitis is the most common cause of ‘acute abdomen’ in young adults. Appendicectomy is the most common surgery performed by a surgeon.However, sometime diagnosis is difficult to make in such case either the diagnosis is missed or patients with normal appendix are operated which lead to increase in morbidity and mortality. The aim of this study was to assess the relationship between hyperbilirubinemia and acute appendicitis and to see whether elevated bilirubin levels have a predictive potential for the diagnosis of appendicular perforation.Methods: This prospective study was carried out in Department of Surgery of National Medical College and Teaching Hospital. A total of 85 patients were included in this study. Data analysis was done using SPSS (Statistical Package for social sciences), version 26.Results: In this study, mean age was 28.86 year. Males (68.23%) outnumbered females (31.76%). Of the 85 patients, 62 patients were diagnosed as simple appendicitis while 23 patients were diagnosed with appendicular perforation. Out of 23 patients of appendicular perforation, 19 patients (82.60%) had raised bilirubin levels. The sensitivity, specificity, positive predicative value and negative predicative value of serum bilirubin as a marker in predicting acute appendicitis and appendicular perforation was 82.60%, 88.70%, 73.07%, 93.22% respectively.Conclusion: Serum bilirubin level appear to be a new laboratory marker in helping to diagnose a case of acute appendicitis.